Enhancing Student Motivation to Learn Using Self-Determination Theory as a Framework : An Exploration of Internal and External Factors in the Context of Sekolah Dasar Negeri 1 Kapoa, Buton Selatan - Suardin; Yusnan, Muhammad; Tarno; Saputra, Lukman; Omar, Saada (The Indonesian Institute of Science and Technology Research, 2023)
This qualitative research study conducted at Sekolah Dasar Negeri 1 Kapoa during the 2020/2021 academic year delves into the intricate web of factors influencing fourth-grade students' motivation to learn, particularly within the context of the pandemic. Through interviews and meticulous data analysis, this research unravels the multifaceted nature of student motivation, shedding light on both internal and external elements that come into play. While physiological factors such as vision and hearing were found to have limited direct influence on motivation, the study highlights the pivotal role of psychological factors. Competence, talents, and family harmony emerged as significant determinants of students' learning motivation. Moreover, external factors proved crucial contributors to this intricate motivational landscape. Parental support, effective teaching methods, peer interactions, and community engagement played vital roles in shaping students' motivation. This research underscores the complexity of student motivation and its dependence on many factors. Understanding these influences is paramount for educators, parents, and policymakers alike. Tailoring teaching approaches, providing robust family support, and creating a nurturing learning environment are key strategies to enhance student motivation and foster academic success. As such, further research and targeted interventions addressing these motivational factors can contribute to the development of more effective, student-centered educational practices.